Pendampingan Penulisan Karya Tulis Ilmiah bagi Mahasiswa Program Doktor di Lingkungan Yayasan Wahdah Islamiyah Sulawesi Selatan - Siti Patimah; A.Gani; Fahrina Yustiasari Liriwati; Abdul Latief Arung Arafah (Karawo : Journal of Community Service (KJCS), 2026)
The ability to write scientific papers is an essential competency for doctoral students, particularly in the preparation of journal articles and dissertations. Various challenges arise in problem formulation, methodological frameworks, reference management, and adherence to academic publication ethics. This Community Service Program aims to provide systematic mentoring in scientific writing for doctoral students at the Wahdah Islamiyah Foundation throughout South Sulawesi. Implementation methods include needs analysis, academic writing workshops, individual mentoring-based writing clinics, and manuscript evaluation using academic rubrics. Results show an improved understanding of article structure, citation techniques, argumentative consistency, and manuscript readiness for submission to accredited national journals. An internal academic community has been established, serving as a sustainable forum to strengthen research culture. Participants reported increased confidence in conducting research, organizing literature reviews, and constructing logical arguments. Overall, this program provides a replicable model to enhance doctoral students’ scientific writing skills, foster academic excellence, and produce high-quality, publishable research that contributes meaningfully to their respective fields.